Opportunity Costs of Gastrointestinal Endoscopic Training in Canada - WT Depew; LC Hookey; SJ Vanner; JA Louw; CE Lowe; MJ Ropeleski; MJ Beyak; A Lazarescu; WG Paterson (Canadian Journal of Gastroenterology)
BACKGROUND: No data exist to define the opportunity costs related to instruction in endoscopic procedures in Royal College of Physicians and Surgeons of Canada-accredited teaching centres. Academic and institutional administrators expect staff to achieve acceptable performance standards. There is a need to measure some of the effects of training activity in the establishment of such standards.